EGF-R is Expressed and AP-1 and NF-κ:B Are Activated in Stromal Myofibroblasts Surrounding Colon Adenocarcinomas Paralleling Expression of COX-2 and VEGF - Panagiotis A. Konstantinopoulos; Gerasimos P. Vandoros; Michalis V. Karamouzis; Maria Gkermpesi; Georgia Sotiropoulou-Bonikou; Athanasios G. Papavassiliou (Cellular Oncology)
Background: COX-2 and VEGF are important triggers of colon cancer growth, metastasis and angiogenesis. Cox-2 promoter contains transcriptional regulatory elements for AP-1 and NF-κ:B transcription factors whilst vegf is a known AP-1 downstream target gene. We investigated whether stromal myofibroblasts surrounding colon adenocarcinomas express COX-2 and VEGF and whether activation of AP-1 and NF-κ:B, as well as expression of EGF-R parallel expression of COX-2 and VEGF in these cells. Methods: Immunohistochemical methodology was performed on archival sections from 40 patients with colon adenocarcinomas. We evaluated c-FOS, p-c-JUN (phosphorylated c-JUN), p-Iκ:B-α (phosphorylated Iκ:B-α), EGF-R, COX-2, NF-κ:B and VEGF expression in stromal myofibroblasts surrounding colon adenocarcinomas. Double immunostaining with a-smooth muscle actin and each antibody was done to verify the expression of these molecules in stromal myofibroblasts. Results: VEGF, p-Iκ:B-α, NF-κ:B, c-FOS, p-c-JUN, EGF-R and COX-2 were expressed in stromal myofibroblasts surrounding colon adenocarcinomas in the majority of cases. EGF-R, p-Iκ:B-α, NF-κ:B, c-FOS and p-c-JUN correlated positively with COX-2 and VEGF expression. Conclusion: Stromal myofibroblasts surrounding colon adenocarcinomas are an important source of VEGF and COX-2 production, while AP-1 and NF-κ:B transcription factors are activated and EGF-R is expressed in these cells and associated with COX-2 and VEGF production.